2014
DOI: 10.1097/md.0000000000000317
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic Characteristics and Survival of Patients With Bone Metastasis in Yazd, Iran

Abstract: To evaluate the clinico-pathological and survival characteristics in patients with bone metastasis.This cross-sectional study was conducted on patients with bone metastasis who referred to Shahid Ramezanzadeh radiation oncology center. For all of the patients studied, demographic and survival information was recorded. SPSS was used to analyze the data.In this study, 89 men (53.3%) and 78 women (46.7%) with bone metastasis were examined. Most of the patients were in the 66 to 87 age range. Breast cancer was the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…A recent study has shown that patient age (OR = 1.024, p < 0.001), the concentration of neuron-specific enolase (OR = 1.212, p = 0.004), and histopathological types (OR = 0.995, p = 0.001) were the independent risk factors for bone metastasis in patients with lung cancer (Zhou et al, 2017; Niu et al, 2014). Another study has shown that clinical stage, histology, and the clinicopathological characteristics were related to a higher risk of bone metastasis in patients with completely resected non-small-cell lung cancer (NSCLC) (Wang et al, 2017; Oliveira, Mello & Paschoal, 2016; Shabani et al, 2014). The risk factors for bone metastasis in SCLC were not frequently reported and in addition to age, race, gender, and N stage, the tumor size was also a risk factor for bone metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has shown that patient age (OR = 1.024, p < 0.001), the concentration of neuron-specific enolase (OR = 1.212, p = 0.004), and histopathological types (OR = 0.995, p = 0.001) were the independent risk factors for bone metastasis in patients with lung cancer (Zhou et al, 2017; Niu et al, 2014). Another study has shown that clinical stage, histology, and the clinicopathological characteristics were related to a higher risk of bone metastasis in patients with completely resected non-small-cell lung cancer (NSCLC) (Wang et al, 2017; Oliveira, Mello & Paschoal, 2016; Shabani et al, 2014). The risk factors for bone metastasis in SCLC were not frequently reported and in addition to age, race, gender, and N stage, the tumor size was also a risk factor for bone metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Bone metastasis is a common problem in advanced cancer patient. Based on the latest data, an estimate of 50% of patients with bone metastases will undergo poorly controlled pain during the course of their disease, 1 , 2 which affects sleep, diet, emotion, and daily activities, with quality of life severely impaired. 3 The current management for bone metastasis are primarily palliative, especially for patients with extensive disease involving multiple bone metastatic sites, a systemic approach including chemotherapy, hormonal therapy, bisphosphonates, and radiopharmaceuticals, is used.…”
Section: Introductionmentioning
confidence: 99%
“…Spinal metastases are common in patients with advanced cancer, second only to lung and liver metastases in incidence [27] . Pain is the most common complication in patients with bone metastases [28] , poorly controlled in half of them [29][30] , which seriously affects quality of life [31] . Traditional treatments for pain related to cancer include surgery, radiation, and chemotherapy, with the goal of reducing or eliminating the cause of pain.…”
Section: Discussionmentioning
confidence: 99%